2011
DOI: 10.1074/jbc.m111.228213
|View full text |Cite
|
Sign up to set email alerts
|

The Leishmania donovani UMP Synthase Is Essential for Promastigote Viability and Has an Unusual Tetrameric Structure That Exhibits Substrate-controlled Oligomerization

Abstract: The final two steps of de novo uridine 5-monophosphate (UMP) biosynthesis are catalyzed by orotate phosphoribosyltransferase (OPRT) and orotidine 5-monophosphate decarboxylase (OMPDC). In most prokaryotes and simple eukaryotes these two enzymes are encoded by separate genes, whereas in mammals they are expressed as a bifunctional gene product called UMP synthase (UMPS), with OPRT at the N terminus and OMPDC at the C terminus. Leishmania and some closely related organisms also express a bifunctional enzyme for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 58 publications
3
32
0
Order By: Relevance
“…The pRP-M vector expresses transgenes from the ribosomal RNA (RRNA) promoter upon integration into the RRNA array and has been used for complementation of ⌬umps parasites (40).…”
Section: Methodsmentioning
confidence: 99%
“…The pRP-M vector expresses transgenes from the ribosomal RNA (RRNA) promoter upon integration into the RRNA array and has been used for complementation of ⌬umps parasites (40).…”
Section: Methodsmentioning
confidence: 99%
“…Orotate phospho-ribosyltransferase, a typical type I phosphoribosyltransferase, contains the "usual" structural elements, a five-stranded ␤-sheet surrounded by a number of helices, usually four, a hood structure involved in the binding of the substrate orotate, and a flexible catalytic loop, which closes the active site on catalysis. The structures of orotate phosphoribosyltransferase from a variety of sources, including S. enterica (223), E. coli (224), S. mutans (225), Plasmodium falciparum (226), and L. donovani (227) have been published.…”
Section: Reactions At the Anomeric Carbon Of Prppmentioning
confidence: 99%
“…Gene sequencing, supported by biochemical studies, has revealed a number of significant differences between the pyrimidine biosynthetic pathways of Leishmania and mammals: 1) the genes encoding the pyrimidine pathway of Leishmania are syntenic (2-5), whereas the mammalian pyrimidine genes are not; 2) the genes encoding the first three enzymes in Leishmania are dis-crete, unlike the mammalian pathway in which there is a single gene encoding a trifunctional protein (6, 7); 3) the last two enzymes of the pyrimidine biosynthetic pathway are expressed as a single bifunctional protein, designated UMP synthase (UMPS), although the domain order in Leishmania and mammalian cells is reversed (3,8); and 4) the UMP synthase of Leishmania is localized within the glycosome (3), a unique peroxisomal-like organelle that is found uniquely among Leishmania and related parasites (9,10). Genetic ablation of either carbamoyl phosphate synthetase (CPS), the first enzyme of pyrimidine biosynthesis, or UMPS in L. donovani confer pyrimidine auxotrophy that can be circumvented by supplementation of the defined growth medium with uracil, uridine, deoxyuridine, cytidine, or deoxycytidine (3,5). Furthermore, both the ⌬cps and the ⌬umps null mutants exhibit a striking collateral supersensitivity to uracil, which is innocuous to wild type parasites, that is not observed with any of the ribonucleosides (5).…”
mentioning
confidence: 99%
“…Parasite Cell Culture-The creation and characterization of ⌬uprt, ⌬cps, and ⌬umps L. donovani lines have been reported previously (3,5). Wild type and null mutant promastigotes were continuously cultured in 26°C in pH 7.4 DME-L medium that was supplemented with 10% Serum Plus (SAFC Biosciences, Lenexa, KS), 1 mg/ml hemin, and 100 M hypoxanthine as a purine source.…”
mentioning
confidence: 99%